2021
DOI: 10.1088/1755-1315/788/1/012172
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of soil physico chemical properties with elevation and geographical directions

Abstract: The core findings of this study revealed that physicochemical properties fluctuate with soil texture and soil class. Sandy soil showed inconsistent variation with geographical directions. Bulk density, lime content, EC and pH decreases with topography and soil elevation while these parameters increased from surface to subsurface soil within a profile. Nitrogen, phosphorus, potassium and micronutrient increased with increase in elevation. All these parameters decreased from surface to subsurface soil. Water hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…lower From 20 mg kg -1 . It was noted from the results of Figure (3), which shows the map of the spatial distribution of ready nitrogen, that most of the study area was within the medium and low level, with an area of 132.68 km2 and 99.12 km2 and a percentage of 53.81% and 40.20% respectively, while the high level had a small area within the studied area, amounting to 14.74 km 2 and not more than 6% of the area of the study area, as well as for dissolved nitrogen where the highest value was 4.8mg.kg -1 . It is also clear from these results that there is a variation in the soil content of ready-made and dissolved nitrogen within the same series as well as the series between them.…”
Section: Nitrogen Content In the Strings Of The Study Sitementioning
confidence: 95%
See 2 more Smart Citations
“…lower From 20 mg kg -1 . It was noted from the results of Figure (3), which shows the map of the spatial distribution of ready nitrogen, that most of the study area was within the medium and low level, with an area of 132.68 km2 and 99.12 km2 and a percentage of 53.81% and 40.20% respectively, while the high level had a small area within the studied area, amounting to 14.74 km 2 and not more than 6% of the area of the study area, as well as for dissolved nitrogen where the highest value was 4.8mg.kg -1 . It is also clear from these results that there is a variation in the soil content of ready-made and dissolved nitrogen within the same series as well as the series between them.…”
Section: Nitrogen Content In the Strings Of The Study Sitementioning
confidence: 95%
“…As for the average, it was clear from Figure (7) that the content of prepared potassium in the soil series was taken in the following order: Seneyah > Sharqat > Al Safa > Jareesh > Hatra, which amounted to 135.36, 133.78, 133.78, 124.50 and 121.46 mg kg -1 , where the highest rate of ready potassium values was In the Chinese series, the lowest rate in the urban series, and in comparison with the ready potassium in the levels set in Table (1), it falls within the average level (100-150) mg.kg -1 . It is observed from Figure (8), which indicates the map of the spatial distribution of the ready potassium content that the average level is in the form of 213.28 km 2 and at a rate of 86.53%, followed by the area of the high level 27.65 km 2 and at a percentage of 11.22% and the low level is 5.55 km 2 and at a rate of 2.25%. Therefore, the variation in the ready potassium may be related to the heterogeneity In the separation of soil texture, gypsum, lime and fertilizer additives.. and other reasons that limit the quantities released from ready potassium, and according to what studies have indicated, the amount of potassium is appropriate in the soil, but it is subjected to stabilization, as its ionic radius is A˚ 1.33 suitable for the absence of mineral holes in the layers and sheets of silica and aluminum [32] and the results are consistent with what [33] found that the presence of ready potassium in the soil in moderate or sufficient proportions may greatly help the plant to withstand drought during the growth stages as well as bear low temperatures at the beginning of the plant life, as well as On helping the plant to perform its biological and physiological functions, and this agrees with [34] and [5], as they showed that potassium plays an important role in raising the plant's ability to withstand drought and increase the plant's resistance to cold.…”
Section: Ready Potassium In the Soil Series Of The Study Areamentioning
confidence: 96%
See 1 more Smart Citation
“…The reason may also be due to the contents of these extracts, in addition to the auxins and cytokines, as they contain salicylic acid, gibberellin GA3 and humic acid, which lead to reducing the stress and tension to which the plant is exposed, which leads to the ability of the roots to absorb nutrients and growth and stimulate vegetative growth as well as drought resistance and tolerance Circumstances2 It is also noted from the traits studied above that there is a significant difference in all treatments when using NPK fertilization. By participating in the synthesis of protein, nucleic acids, DNA, and RNA-all of which play important roles in cell division and elongation [15,16], and by participating in the formation of the amino acid Tryptophan, the initiator of the formation of auxin IAA, which has a direct role in cell divisions and elongation nitrogen improves vegetative characteristics. Protein synthesis and other substances necessary for growth, such as carbohydrates, are inhibited in its absence [17].…”
Section: The Fresh Weight (Leafgm)mentioning
confidence: 99%
“…Grain yield of wheat can be reduced with the reduction in irrigation level, whereas the addition of biochar might improve water use efficiency and plant essential nutrients uptake (Jan et al, 2012). Previously it is reported that biochar with different irrigation regimes may show high efficiency and booted yield (Ali et al, 2020;Ali et al, 2021;Imran et al, 2020c;Imran et al, 2021d;Imran et al, 2021e;Imran, 2015b). Donaldson et al (2013) reported that irrigation regimes resulted in increased wheat straw production and generally higher grain yield compared with various carbon sources.…”
Section: Introductionmentioning
confidence: 99%